The execution of commercial contracts under the CIGS-GAFTA-FOSFA models in the regional context (Papeles, 2022)
The goal of this academic exercise is to verify in a somewhat tangential way how the performance of some contracts is carried out in the Latin American regional legal context; all this related to the three international main regulations in the field such as: the Vienna Convention of 1980 on the international sale of goods, the regulation of the Grain and Trade Feed Association, and that of the Federation of Oils, Seeds, and Fats Associations. In this case, we will seek to identify the most relevant aspects offered by such regulations in terms of the way in which a contract concluded under them must be executed in any of the regional legal systems. In this sense, we will show some aspects that, in our opinion, make this class of norms a novel and pragmatic legal specialty.
Keywords: Conflicts of laws; performance; public policy; international contracts; Private International Law